Pharmacists’ perception about providing services to patients with headaches in primary care - Homšek, Ana; Jovanović, Marija; Roganović, Maša; Kovačević, Milena; Ćulafić, Milica; Vezmar Kovačević, Sandra; Vučićević, Katarina; Miljković, Branislava (Archives of Pharmacy, 2022)
Since headaches represent one of the most common disabling conditions in the world1 and can be treated with over-the-counter drugs, the role of pharmacists in caring for these patients has been recognized as very important. The research aim was to review primary health care pharmacists’ perception regarding patient service they provide and the conducted education devoted to headaches. Data were collected through a survey adapted from the published article2 and analysed in SPSS and Microsoft Excel. The survey was completed by 43 primary health care pharmacists (90.7% women, age 27-64). The survey reliability was verified using the Cronbach’s test (αB = 0.727; αC = 0.880). Most of the surveyed pharmacists believe that they listen carefully to patients with headaches (65% always, 27.9% often), 44.7% always check interactions, while 86.04% always advise the patient on proper drug administration. However, 34.88% report that they never contact doctors if the drug is expensive, not reimbursable or causes an adverse reaction that limits its use, and 32.55% only sometimes do so. Most pharmacists believe education was useful to better understand patients and counsel them about headaches (97.67-100%), while a slightly smaller percentage (93.02%) thinks it helped them learn to identify a migraine patient and refer him to a doctor. The perception of most pharmacists is that they advise patients on headache treatment even without prior education, but after it, the service would be more complete. The study results indicate that future education should focus on improving communication with doctors.